Finite size corrections to the equation of state for nuclear matter near the phase transition hadron gas to quark gluon plasma - Schnabel, Allard Guntram (Department of Chemistry, 2023)
It is widely accepted that the finite size of the hadrons must be taken into account in a thermodynamic description of the hadron gas near the phase transition to quark gluon plasma. Existing thermodynamic models introducing a .correction due to the finite size of the particles are reviewed and discussed. A new model to describe dense nuclear matter is developed. The model takes into account the different quantum statistical distributions of the hadrons. The grand canonical pressure partition function is used. to obtain the thermodynamic limit. The grand canonical partition function is restricted so that only those states where the extended particles fit into the volume of the system, are counted. The configuration space is reduced accordingly. The hadrons are described as MIT bags. The size of the particles depends on the pressure in the system. The pressure in the system compresses the hadrons which leads to an increase of the mass of the hadrons according to the MIT bag equation. The size of the particles is determined by the minimum of the grand canonical potential. A consistent thermodynamic theory is obtained. The equation of state for hadronic matter is discussed for the special cases, zero temperature and zero chemical potential, before the general case of finite temperature and finite chemical potential is used to construct a first order phase transition from hadron gas to quark gluon plasma. At high densities the influence of the description of the hadrons as MIT bags becomes significant. It is found that the phase transition is strongly dependent on the value chosen for the bag constant and the application of as corrections. Therefore ~reliable value of the bag constant and a generally accepted theory for as corrections are essential to obtain a good thermodynamic description of the phase transition from hadron gas to quark gluon plasma.